2012
DOI: 10.1016/j.metabol.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weight loss and exercise on chemerin serum concentrations and adipose tissue expression in human obesity

Abstract: Chemerin is a chemoattractant adipokine that regulates adipogenesis and may induce insulin resistance. Chemerin serum concentrations are elevated in obese, insulin-resistant, and inflammatory states in vivo. Here we investigate the role of omental (OM) and subcutaneous (SC) adipose tissue chemerin and CMKLR1 messenger RNA (mRNA) expression in human obesity. In addition, we test the hypothesis that changes in chemerin serum concentrations are primarily associated with reduced body fat mass in the context of 3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
196
2
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(237 citation statements)
references
References 25 publications
30
196
2
9
Order By: Relevance
“…Circulating chemerin levels are known to be associated with obesity in humans (11,15,26,27,28,29). In this study, hepatic chemerin mRNA expression was found to be significantly associated with BMI (R 2 Z0.296; PZ0.039), waist circumference (R 2 Z0.397; PZ0.005), and body fat percentage (R 2 Z0.378; PZ0.008).…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Circulating chemerin levels are known to be associated with obesity in humans (11,15,26,27,28,29). In this study, hepatic chemerin mRNA expression was found to be significantly associated with BMI (R 2 Z0.296; PZ0.039), waist circumference (R 2 Z0.397; PZ0.005), and body fat percentage (R 2 Z0.378; PZ0.008).…”
Section: Resultsmentioning
confidence: 52%
“…adipocytokines (8), and is known to be expressed in the WAT of mice, Psammomys obesus, and humans (9,10,11,12,13,14,15). Chemerin exerts its effects at least in part (16,17) via the orphan G-proteincoupled receptor chemokine-like receptor 1 (CMKLR1) (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, infusion of chemerin into the mouse modestly elevated blood pressure (20), and chemerin has been suggested to reduce nitric oxide signaling in the rat aorta (29). Understanding the functions of chemerin is important, because circulating levels of chemerin can be reduced and health can be improved through a number of interventions that include bariatric surgery and exercise (7,22,24,28,30,34,39,44). Other pathologies, such as arterial stiffness (54) syndrome (15,18), have been associated with elevated chemerin levels.…”
Section: Discussionmentioning
confidence: 99%
“…CD68 mRNA in obese patients is higher than in normal people, and it has been proven that there is a correlation between YKL-40 and CR68 mRNA levels. Therefore, we can speculate that YKL-40 is involved in immune and inflammatory responses in adipocytes (El-Mesallamy et al, 2011;Chakaroun et al, 2012).…”
Section: Discussionmentioning
confidence: 99%